Iowa Birdline update, November 4-7, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of Iowa Birdline updates for November 4-7, 1991. The highlights for the updates include sightings of a Common Ground-Dove, Black-legged Kittiwake at two locations, a Western Grebe and a very late Forster's Tern. Also included are handwritten notes with sightings of a Pacific Loon, Glaucous Gull and an American Kestrel. Epson - sheet feed/flatbed